Nickel(II) Assisted Determination of Some Reducing Sugars with Alkaline Ferricyanide - Muralikrishna, U.; Sivaramakrishna, A. (Asian Journal of Chemistry, 2010)
Conditions were developed for titrimetric quantitative determination of some reducing sugars such as glucose, galactose, fructose, lactose, maltose and inverted sucrose with alkaline ferricyanide as an oxidizing agent using nickel(II) sulphate as catalyst and its dimethylglyoxime complex as an indicator. The reaction between glucose and ferricyanide has been found to correspond to a definite stoichiometry. The products obtained by the oxidation of glucose. are isolated and identified. The present proposed method is successfully applied to the determination of lactose in milk and sucrose content in commercial cane sugar products.